2020
DOI: 10.1186/s40104-019-0423-9
|View full text |Cite
|
Sign up to set email alerts
|

Branched chain amino acids alter fatty acid profile in colostrum of sows fed a high fat diet

Abstract: Background: Branched chain amino acids (BCAAs) are important substrates for milk protein synthesis in the mammary gland, and are tightly related to lipid metabolism. No study has been performed examining the role of BCAAs with high fat diets on milk fat synthesis. This study was designed to investigate the effect of dietary BCAAs on growth performance of piglets, progeny body weight, and milk fat composition in sows fed a high fat diet. Four diets (CON = control diet; HF = high fat diet with 8% soybean oil; HF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…However, this study is the rst one using α-GML for sow nutrition. We found that dietary α-GML inhibited de novo lipogenesis of the mammary gland (lower percentage of the sum of C8:0, C10:0, C12:0, and C14:0 in milk), which consistent with published studies in sows [33]. Consistent with the experimental diet treatment, C12:0 in colostrum and milk was higher from sows-fed α-GML than the control sows.…”
Section: Discussionsupporting
confidence: 90%
“…However, this study is the rst one using α-GML for sow nutrition. We found that dietary α-GML inhibited de novo lipogenesis of the mammary gland (lower percentage of the sum of C8:0, C10:0, C12:0, and C14:0 in milk), which consistent with published studies in sows [33]. Consistent with the experimental diet treatment, C12:0 in colostrum and milk was higher from sows-fed α-GML than the control sows.…”
Section: Discussionsupporting
confidence: 90%
“…We measured very low concentrations of fatty acids (4.5 μg per mg of CHC, Table S2 , refs. [ 81 , 82 , 83 ]) in CHC. With such low concentrations of fatty acids, we could not perform the treatment of primary cells.…”
Section: Discussionmentioning
confidence: 99%
“…Branched-chain AAs (BCAAs; such as isoleucine, valine), besides their recently asserted role in glucose metabolism [ 94 , 95 ], are also linked with fatty acids metabolism. Recent evidence suggests catabolism of these BCAAs contributes to odd chain and long-chain FAs synthesis [ 96 , 97 , 98 ]. The presently observed negative correlation between BCAAs and some FAs in rheophilic cyprinids body (barbel, nase, asp and vimba bream; Figure 3 ) is interesting.…”
Section: Discussionmentioning
confidence: 99%